Role of Traffic Network in Monitoring Crime and Violence Patterns in Karachi - Umair bin Zamir; Masood, Hina (Journal of Basic & Applied Sciences, 2021)
Crime and geographical accessibility has very special relationship, if monitored on appropriate time it could resolve many complex issues of the crime dynamics. Karachi being the largest city of Pakistan is also very high in the intensity of street crimes that often has very close relationship with the network of the roads. This paper will assess the potential of Geographical Information Systems (GIS) for the analysis of crime pattern and its relationship with the road network in Karachi that would be beneficial for various crime agencies. Present research aims to provide a collective set of methods and techniques for geospatial analysis and 3D mapping of crime scenes. After identification of Hotspots assessment of relationships between robbery or snatching clusters and their spatial neighborhood is initiated by including the urban milieu. For obtaining the desired target copious geospatial data as well as a three-dimensional model is included for analysis. The combined and mutual effort of crime mapping methods with modern 3D modelling helps to facilitate on the spot clutch of multipart spatial phenomena in mapping of crime, and fruitful for both, the communal and responsible decision makers.